Results of Research on the Aquatic Plant Carolina Azolla (Azolla Caroliniana Willd) - J. Ch. Urinov; Ass. Kh.B.Meylieva; O'.A.Nazarov; M.Mukhtorova (Zien Journals, 2022)
The article presents the biological characteristics and distribution of high water plants Carolina Azolla (Azolla caroliniana willd.). Information on the level of reduction of water mineralization by the growth, development, reproduction of aquatic plants in the collector and ditch waters is given
Keywords: High water plants; pistia; azolla; biomass